Rancangan Sistem Informasi Pengelolahan Data Kriminal Pada Polsek Jaluko - Adhiatma, Novri (Lembaga Penelitian Dan Pengabdian Masyarakat - STMIK Nurdin Hamzah Jambi, 2016)
During this time, the data processing system at the Police Jaluko criminals have used a computer but not as optimal as possible, so it takes a long time to search criminal data on police Jaluko. The purpose of this thesis was to study the data processing system at the police criminal Jaluko, identify weaknesses that may be in it and designed a new application program using Visual Basic 6.0. With the data processing system is expected to change the old system to the new system. By using Visual Basic 6.0, changes to the data processing system is intended facilitate processing of criminal data on police Jaluko, so that later the data can be processed properly and quickly. The results of this study demonstrate using data processing applications properly designed, data validation has been able to do since pengimputan, process data and reports presented during the data entered is true.